A prospective pilot study to identify a myocarditis cohort who may safely resume sports activities 3 months after diagnosis - Patriki, D.; Baltensperger, N.; Berg, J.; Cooper, L. T.; Kissel, C. K.; Kottwitz, J.; Lovrinovic, M.; Manka, R.; Scherff, F.; Schmied, C.; Tanner, F. C.; Luescher, T. F.; et al. (Journal of Cardiovascular Translational Research, 2020)
International cardiovascular society recommendations to return to sports activities following acute myocarditis are based on expert consensus in the absence of prospective studies. We prospectively enrolled 30 patients with newly diagnosed myocarditis based on clinical parameters, laboratory measurements and cardiac magnetic resonance imaging with mildly reduced or preserved left ventricular ejection fraction (LVEF) with a follow-up of 12 months. Cessation of physical activity was recommended for 3 months. The average age was 35 (19-80) years with 73% male patients. One case of non-sustained ventricular tachycardia was recorded during 48-h-Holter electrocardiogram. Except for this case, all patients were allowed to resume physical exercise after 3 months. At 6- (n = 26) and 12-month (n = 19) follow-up neither cardiac events nor worsening LVEF were recorded. The risk of cardiac events at 1 year after diagnosis of myocarditis appears to be low after resumption of exercise after 3 months among patients who recover from acute myocarditis.